Rapid Naming in Brazilian Students with Dyslexia and Attention Deficit Hyperactivity Disorder - Alves, Luciana Mendonça; Siqueira, Cláudia M.; Ferreira, Maria do Carmo Mangelli; Alves, Juliana Flores Mendonça; Lodi, Débora F.; Bicalho, Lorena; Celeste, Letícia C. (Frontiers in Psychology, 2016)
Introduction: The effective development of reading and writing skills requires the concerted action of several abilities, one of which is phonological processing. One of the main components of phonological processing is rapid automatized naming (RAN)—the ability to identify and recognize a given item by the activation and concomitant articulation of its name. Objective: To assess the RAN performance of schoolchildren with dyslexia and attention deficit hyperactivity disorder (ADHD) compared with their peers. Methods: In total, 70 schoolchildren aged between 8 and 11 years participated in the study. Of these, 16 children had a multiprofessional diagnosis of ADHD while 14 were diagnosed with dyslexia. Matched with these groups, 40 schoolchildren with no history of developmental impairments were also evaluated. The RAN test was administered to assess the length of time required to name a series of familiar visual stimuli. The statistical analysis was conducted using measures of descriptive statistics and the 2-sample t-test at the 5% significance level. Results: The performance of the group with dyslexia was inferior to that of the control group in all tasks and the ADHD group had inferior performance for color and letters-naming tasks. The schoolchildren with dyslexia and those with ADHD showed very similar response times. Age was an important variable to be analyzed separately. As they aged, children with typical language development had fast answers on colors and digits tasks while children with dyslexia or ADHD did not show improvement with age. Conclusions: The schoolchildren with dyslexia took longer to complete all tasks and ADHD took longer to complete digits and objects tasks in comparison to their peers with typical development. This ability tended to improve with age, which was not the case, however, with schoolchildren who had ADHD or dyslexia.